Pengaruh Al-qur’an terhadap kesehatan jasmani: Harmoni spiritual dan fisik - Maziyya, Nanda (Maliki Interdisciplinary Journal, 2025)
Listening to the Qur’an can greatly affect human health. The aim of this article is to investigate how listening to the Qur’an impacts one's health. This research uses a literature review as a method to find relevant results from academic databases and official sources. Various empirical and scientific studies have been conducted on this issue and found that listening to the Qur’an has many benefits for physical and mental health. This study concluded that listening to the Qur’an increases concentration, lowers blood pressure, improves sleep quality, and reduces stress. In addition, listening to the Qur’an is associated with an increase in endorphins. Listening to the Qur’an regularly can improve the body's defenses against disease and the immune system. To support these claims more strongly, further research is needed. Therefore, to improve our understanding of the relationship between listening to the Qur’an and human health, more detailed and targeted research will be conducted in the future.